1966
DOI: 10.1002/app.1966.070100506
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of ultrasonic wave velocities in plastics as functions of temperature. I. Common plastics and selected nose‐cone materials

Abstract: synopsisAn experimental study was conducted to determine previously unavailable data showing the relationship between temperature and the velocity of longitudinal ultrasonic waves through several plastics. The ultrasonic frequencies used were between 1 and 10 Mc./sec., and the temperature range covered was between room temperature and 100°C. Velocity-temperature curves were determined for nylon, a high-and a low-density polyethylene, Plexiglas, Teflon, and for several reentry vehicle nose-cone materials, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1966
1966
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Ultrasonic transducer probes were used in a two-probe 'send and receive' mode. A control module excites a pulse in the sender probe, and amplifies any signals detected by the receiver probe, producing a periodic trace that can be monitored on an oscilloscope [11]. The time lag from the incident pulse to the point of initial rise of the received pulse is deemed to be the travel time.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonic transducer probes were used in a two-probe 'send and receive' mode. A control module excites a pulse in the sender probe, and amplifies any signals detected by the receiver probe, producing a periodic trace that can be monitored on an oscilloscope [11]. The time lag from the incident pulse to the point of initial rise of the received pulse is deemed to be the travel time.…”
Section: Methodsmentioning
confidence: 99%
“…The settings used for the calibration is summarized in Table 3. For viscoelastic materials, such as HDPE at the temperatures studied here, the attenuation coefficient and phase velocity will vary with temperature [45,46]. Therefore, since the AST temperature will vary seasonally, the effect of temperature on wave velocity was evaluated.…”
Section: Ultrasonic Testing (Ut)mentioning
confidence: 99%
“…The value of this property, made available by the manufacturer, is most certainly obtained from quasi-static tests. However, several authors have previously reported that this property is frequency dependent [11,[30][31][32][33]. Some of these authors suggest that the dynamic elastic modulus should be measured using the ultrasonic technique due to its non-destructive character.…”
Section: Dynamic Young's Modulus Measurementmentioning
confidence: 99%